Parenting Development Strategy in Stimulating the Growth and Development of Early Childhood for the Buddhist Community in Plandi and Lemungsur Villages, Central Java - Metri, Gustiya Gandha; Astana, Astri Chintya; Permatasari, Tisya; Susijati, Susijati (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to describe parenting education in stimulating children's growth and development through the use of objects in the surrounding environment. Of course, this is also in line with the aim of research activities regarding parenting development strategies for parents in fostering early childhood development in the Lemungsur village community, Kebumen district and the community in Plandi village, Banyumas district. The researcher used a qualitative descriptive method. Data collection techniques use observation, interview and documentation techniques. Data collection tools are observation sheets, interview guides and documentation. Data processing was carried out using qualitative descriptive analysis. And the results of the research show that parenting training strategies in stimulating early childhood growth and development are really needed by the community in the region. The level of parental education also influences understanding of early childhood care, because almost 80% of local people do not think that using objects in the surrounding environment can be useful for stimulating the growth and development of early childhood. So with this research, the results obtained are that the public can understand good parenting patterns and uniting as parents is an important key to optimizing the stimulation of early childhood growth and development.